Changes in phosphate fractions in prawn aquaculture system at different stages of cropping - Ashraf, P Muhamed; Pillai, A G Gopalakrishna (Indian Journal of Fisheries, 2011)
Studies were conducted to evaluate the flux of phosphate fractions in prawn aquaculture systems in one cropping season and its relation with water and sediment characteristics. The results from the samples of two scientific and one natural culture ponds revealed that there was no loosely bound P in all the three stages of cropping. Al bound P increased significantly at the harvest stage compared to initial stage. This was attributed mainly to readsorption of P on aluminium hydroxides. The utilisation of iron bound P was in the late juvenile stage and that of Ca bound P at the harvest stage. The inorganic P increased from juvenile to late juvenile stage and at harvest it recorded 22.5-36.7% decrease than the late juvenile stage. In the natural pond total P was reduced due to mineralisation of P. 50% of the organic bound P was mineralised in natural pond during initial to late juvenile stage whereas, organic P has only minor role in scientific systems